Manufacturing method of pantograph slide plate
Through the graphitization sintering process of high-purity carbon materials, asphalt and copper powder and titanium carbide, the problem of uneven guiding performance of traditional pantograph skateboards is solved, and the effect of balanced conductivity and extended service life is achieved.
Patent Information
- Application Number
- CN202310700519.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-13
- Publication Date
- 2024-12-13
AI Technical Summary
Traditional pantograph skateboard manufacturing methods lead to uneven guiding performance, affecting the conductive performance and service life.
High-purity carbon materials, asphalt, copper powder and titanium carbide are used to mix them, and dense carbon-based electrical contact materials are formed through graphitization sintering process, and embedded them into the titanium pantograph type to form a titanium lightweight high-speed iron pantograph slide. .
It realizes the self-weight reduction and balanced conductivity of the pantograph skateboard, with good operating effect, long service life, low power consumption level and low production cost.
Smart Images

Figure CN119118669A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of electrical contact materials, and in particular, to a method for manufacturing a pantograph slide plate. Background Art
[0002] Electrical contact materials (also known as contact materials or contact materials) are one of the important materials in the process of power transmission and signal transmission. In the electrical and electronic fields, electrical contact materials are mainly used as electrical contacts, conductive brushes, collector rings, commutator segments, rectifier segments and connectors, etc., and are important functional components in the electrical on-off link. The performance of these electrical contact components directly affects the reliability, stability, accuracy and service life of the applied products and the entire system. At the same time, as various products develop towards high precision and miniaturization, higher requirements are placed on the performance of electrical contact components: electrical contact components must meet application requirements in terms of resistivity, contact resistance, density, chemical composition, resistance to fusion welding, corrosion resistance, weldability, reliability, stability, accuracy and service life. With the development of electronic technology, the research and production of electrical contact materials have received great attention from the industry.
[0003] In various fields involving electrical and electronic technology, communication technology, and automatic control technology, electrical contact not only undertakes important functions of power transmission and signal transmission, but is also the part of the entire system that is most prone to failure. Therefore, it is of great significance to develop new electrical contact materials and improve their reliability and service life.
[0004] In the prior art, the production of high-speed rail pantograph slides usually uses high-purity carbon materials, non-ferrous metal conductive materials and binders as raw materials to press and sinter carbon strips, and use stainless steel plates to hoop the edges. Usually, the high-purity carbon material requires a carbon content greater than 98.97%, and at the same time limits the silicon iron oxide elements that affect the conductivity to less than 0.03%. The main body of the non-ferrous metal conductive material is ultra-fine ultra-pure copper powder with a particle size greater than 200 mesh and a purity greater than 99%. The volume density of the sintered carbon fiber material is less than 2.8%, the volume density of the metal-impregnated carbon material is less than 4.0, and the volume density of the multi-component carbide composite material (MCC) is less than 3.8. However, the use of stainless steel hoops leads to an increase in overall weight.
[0005] Therefore, the pantograph slide plate manufactured by the conventional manufacturing method has uneven guiding performance, which is a technical problem that technical personnel in this field urgently need to solve.
[0006] The above information disclosed in the background section is only for enhancing understanding of the background of the present application and therefore it may contain information that does not form the prior art known to a person of ordinary skill in the art. Summary of the invention
[0007] An embodiment of the present application provides a method for manufacturing a pantograph slide plate to solve the technical problem of uneven guiding performance of a pantograph slide plate manufactured by a conventional method for manufacturing a pantograph slide plate.
[0008] The present application provides a method for manufacturing a pantograph slide plate, comprising the following steps:
[0009] Step S1: mixing high-purity carbon material, asphalt, copper powder, and titanium carbide, and then adding a binder to form a five-component mixture; wherein titanium carbide is used as a dopant;
[0010] Step S2: pressing and preforming the five-component mixture, and then pre-graphitizing and sintering it to obtain a pantograph carbon-based electrical contact material;
[0011] Step S3: The surface of the pantograph carbon-based electrical contact material obtained by graphitization sintering is treated and conformed to form a carbon strip, and the carbon strip is embedded in the titanium pantograph mold to obtain a titanium lightweight high-speed rail pantograph slide plate.
[0012] The embodiment of the present application adopts the above technical solution, which has the following technical effects:
[0013] In the manufacturing method of the pantograph skateboard of the embodiment of the present application, titanium carbide is used as a dopant in step S1. The sintering method adopted in step S2 is graphitization sintering. The graphitization sintering method makes the carbon-based electrical contact material of the pantograph have dense characteristics and reasonable porosity. On the one hand, the reasonable porosity reduces the self-weight of the skateboard; on the other hand, the pore size is uniform, and the copper powder immersed in the carbon-based electrical contact material of the pantograph is uniform, so that the conductive performance is balanced. The pantograph skateboard manufactured by the manufacturing method of the pantograph skateboard of the embodiment of the present application has low self-weight and balanced conductive performance, which in turn has the advantages of good operating effect, long service life, low power consumption level and low production cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0015] Figure 1 This is a flow chart of a method for manufacturing a pantograph slide plate according to an embodiment of the present application. DETAILED DESCRIPTION
[0016] In order to make the technical solutions and advantages in the embodiments of the present application more clearly understood, the exemplary embodiments of the present application are further described in detail below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present application, rather than an exhaustive list of all the embodiments. It should be noted that the embodiments in the present application and the features in the embodiments can be combined with each other without conflict.
[0017] Embodiment 1
[0018] like Figure 1 As shown, a method for manufacturing a pantograph slide plate according to an embodiment of the present application comprises the following steps:
[0019] Step S1: mixing high-purity carbon material, asphalt, copper powder, and titanium carbide, and then adding a binder to form a five-component mixture; wherein titanium carbide is used as a dopant;
[0020] Step S2: pressing and preforming the five-component mixture, and then pre-graphitizing and sintering it to obtain a pantograph carbon-based electrical contact material;
[0021] Step S3: The surface of the pantograph carbon-based electrical contact material obtained by graphitization sintering is treated and conformed to form a carbon strip, and the carbon strip is embedded in the titanium pantograph mold to obtain a titanium lightweight high-speed rail pantograph slide plate.
[0022] In the manufacturing method of the pantograph skateboard of the embodiment of the present application, titanium carbide is used as a dopant in step S1. The sintering method adopted in step S2 is graphitization sintering. The graphitization sintering method makes the carbon-based electrical contact material of the pantograph have dense characteristics and reasonable porosity. On the one hand, the reasonable porosity reduces the self-weight of the skateboard; on the other hand, the pore size is uniform, and the copper powder immersed in the carbon-based electrical contact material of the pantograph is uniform, so that the conductive performance is balanced. The pantograph skateboard manufactured by the manufacturing method of the pantograph skateboard of the embodiment of the present application has low self-weight and balanced conductive performance, which in turn has the advantages of good operating effect, long service life, low power consumption level and low production cost.
[0023] The components of the five-component mixture and the purity requirements of each component are as follows:
[0024] In implementation, the content of carbon in the high-purity carbon material is greater than or equal to 95.3% and less than or equal to 98.7% by weight;
[0025] In practice, the carbon content in the asphalt is greater than 45% by weight of fixed carbon.
[0026] In practice, the content of copper in the copper powder is not less than 99% by weight.
[0027] In practice, the titanium carbide is titanium carbide prepared by carbon thermal reduction of anatase titanium dioxide, wherein the titanium content of the titanium carbide is greater than or equal to 83% by weight, and the free carbon is less than or equal to 1%.
[0028] In practice, the binder may be asphalt or polyvinyl alcohol, etc. When asphalt is used as the binder, the asphalt is required to be high quality, low in sulfur, low in ash, and stable and controllable in volatile matter, and the main part of the sintering process is converted into carbon.
[0029] In practice, the proportion of the five-component mixture in the ingredients is as follows:
[0030] The proportion of high-purity carbon materials is less than or equal to 58% and less than or equal to 70%;
[0031] The proportion of asphalt is less than or equal to 13% and less than or equal to 17%;
[0032] The proportion of copper powder is less than or equal to 2.5% and less than or equal to 4.5%;
[0033] The proportion of titanium carbide is less than or equal to 2.5% and less than or equal to 4.5%;
[0034] The proportion of adhesive is less than or equal to 12% and less than or equal to 16%.
[0035] As a preferred method, the proportion of the five-component mixture in the ingredients is as follows:
[0036] The proportion of high-purity carbon materials is less than or equal to 62%;
[0037] Asphalt accounts for less than or equal to 16%;
[0038] The proportion of copper powder is less than or equal to 3.5%;
[0039] The proportion of titanium carbide is less than or equal to 3.5%;
[0040] The proportion of adhesive is less than or equal to 15%.
[0041] During implementation, in step S2, when the five-component mixture is pressed for pre-molding, the pressure is maintained at 400t; in step S2, a pre-graphitization sintering chamber is prefabricated, specifically, sintering at 1000°C for 6h in an electromagnetic induction sintering furnace, the heating curve is maintained at 200°C per hour, and the cooling curve is also maintained at 200°C per hour.
[0042] In the implementation, in step S3, the carbon-based electrical contact material of the pantograph is embedded in the titanium pantograph mold, specifically:
[0043] The pantograph carbon-based electrical contact material is embedded in the outer hoop edge metal frame, wherein the outer hoop edge metal frame is titanium metal with a purity greater than 99% and a thickness of 1.0 mm.
[0044] During implementation, in step S3, the surface of the pantograph carbon-based electrical contact material obtained by graphitization sintering is processed and conformed, that is, turning finishing and surface treatment are performed, and the processing amount does not exceed 10% of the total amount.
[0045] Specifically, the tensile strength and electrical properties of the carbon strips were tested, the density of the carbon strip (pure carbon) was ≤1.8g / cm3, the density of the carbon strip (metal-impregnated carbon) was ≤4.0g / cm3, and the density of the carbon strip (MCC) was ≤3.8g / cm3;
[0046] The flexural strength of the carbon bar (pure carbon) is ≥30MPa, the flexural strength of the carbon bar (metal-impregnated carbon) is ≥50MPa, and the flexural strength of the carbon bar (MCC) is ≥60MPa; the carbon bar (pure carbon) is a pure carbon carbon bar, the carbon bar (metal-impregnated carbon) is a carbon bar impregnated with metal carbon, and the carbon bar (MCC) is a carbon bar manufactured by the manufacturing method of the pantograph slide of the present application; pure carbon carbon bars and metal-impregnated carbon carbon bars are prior art.
[0047] The compressive strength of carbon bar (pure carbon) is ≥40MPa, the compressive strength of carbon bar (metal impregnated) is ≥100MPa, and the compressive strength of carbon bar (MCC) is ≥100MPa;
[0048] Carbon bar (pure carbon) impact toughness ≥ 0.1J / cm2, carbon bar (metal impregnated) impact toughness ≥ 0.15J / cm2, carbon bar (MCC) impact toughness ≥ 0.2J / cm2;
[0049] The electrical characteristics of carbon strip (pure carbon) are resistance ≤40μΩ·m at 20℃, the electrical characteristics of carbon strip (metal impregnated) are resistance ≤12μΩ·m at 20℃, and the electrical characteristics of carbon strip (MCC) are resistance ≤2μΩ·m at 20℃.
[0050] Compared with the prior art, the manufacturing method of the pantograph slide plate of the present application has the following advantages:
[0051] (1) The present invention can effectively utilize the characteristics of C, Cu, and Ti to dope high-purity titanium carbide with dopants to form TiB2 / Ti3SiC2 / Cu pantograph slide material, TiC-Cu electrical contact material, and graphene CuTiSn electrical contact material, which helps to solve the problem of efficient electrical conduction of high-speed rail pantograph slides.
[0052] (2) The present application uses a mixture of high-purity carbon material, asphalt, copper powder, and titanium carbide and then adds a binder to form a uniform five-component mixture. The five-component mixture is pre-formed and graphitized and sintered using a specific model. The electrical contact material strength, thermal stability and density of the pantograph slide plate are finally formed, which can improve the conductivity and temperature adaptability under static and dynamic rated currents, and reduce impact fracture failure.
[0053] (3) The present application uses pure titanium plate hoops, which can reduce weight by 15% under the same conditions, with a significant lightweight effect.
[0054] In the manufacturing method of the pantograph slide plate of the embodiment of the present application,
[0055] The specific detailed steps of step S1 are as follows:
[0056] Step S11: Weigh the high-purity carbon material, asphalt, copper powder and titanium carbide separately, and then reasonably add the carbon asphalt binder.
[0057] For example, the carbon content of high-purity carbon materials, asphalt, and copper powder:
[0058] The weight percentage of the carbon-based electrical contact material of the pantograph can be controlled to be greater than or equal to 95% and less than or equal to 98%;
[0059] The percentage of ingredients in the five-component mixture is greater than or equal to 80% and less than or equal to 82%;
[0060] When preparing the mixture for entering the furnace, the amount of binder can account for a percentage of greater than or equal to 15% and less than or equal to 17% of the total weight of the graphitization sintering raw materials, and 19% of the volatile matter of the asphalt binder volatilizes during the graphitization sintering process; the titanium carbide is controlled according to 1% to 1.2% of the titanium content after the mixed graphitization sintering, and the ingredient percentage is 1.2% to 1.44%; the copper powder is controlled according to 1.5% to 2% of the copper content after the mixed graphitization sintering, and the ingredient percentage is 1.395% to 1.86%.
[0061] In the present application, the expressions m% to n% mean that they are greater than or equal to m% and less than or equal to n%.
[0062] Step S12: Mix the high-purity carbon material with asphalt, copper powder and titanium carbide in a certain proportion at a certain temperature and with a certain amount of binder, and the kneading process is suitable for a mixing-kneading screw. ① Dry mixing for 25min to 35min, during dry mixing, various raw materials are mixed evenly, and solid carbonaceous materials of different particle sizes are evenly mixed and filled to improve the density of the mixture; ② After adding coal tar, wet mixing for 45min to 50min, so that the dry material and asphalt are evenly mixed, and the liquid asphalt is evenly coated and infiltrated on the surface of the particles to form a layer of asphalt bonding layer, which bonds all materials together, and then forms a homogeneous plastic paste, which is conducive to molding; ③ Part of the coal tar penetrates into the internal voids of the carbonaceous material, further improving the density and bonding of the paste.
[0063] The specific detailed steps of step S2 are as follows:
[0064] Step S21: The high-purity carbon material is mixed with asphalt, copper powder, titanium carbide and asphalt to produce a paste that is plastically deformed under the external force applied by the molding equipment, and finally a green body with a certain shape, size, density and strength is formed. The molding is suitable for molding (vertical hydraulic press), extrusion (horizontal hydraulic extruder, screw extruder), vibration molding (vibration molding machine) and isostatic pressing (isostatic pressing machine). ① The kneaded material is cooled for 20-30 minutes through disc cooling, cylinder cooling, kneading cooling and other methods to discharge volatiles, reduce to a suitable temperature (90-120℃) and increase bonding force, so that the paste block size is uniform and conducive to molding; ② Loading: press raising baffle ---- feeding in 2-3 times ---- compacting at 4-10MPa; ③ Pre-pressing: pressure 20-25MPa, time 3-5min, and vacuuming at the same time; ④ Extrusion: press lowering baffle ---- 5-15MPa extrusion ---- shearing ---- turning into cooling water tank; ⑤ Technical parameters of extrusion: compression ratio, press chamber and nozzle temperature, cooling material temperature, pre-pressing pressure time, extrusion pressure, extrusion speed, cooling water temperature; ⑥ Inspection of green billet: volume density, appearance knocking, and analysis.
[0065] Step S22: The pre-prepared carbon strip green body is placed in a specially designed heating furnace under the protection of the filler for high-temperature roasting heat treatment to carbonize the coal tar pitch in the green body. ① The asphalt coke formed after the carbonization of the coal tar pitch consolidates the carbonaceous aggregate and the powder particles together. The roasted carbon product has high mechanical strength, low resistivity, good thermal stability and chemical stability. Roasting is one of the main processes in the production of carbon products, and is also an important part of the three major heat treatment processes in the production of graphite electrodes. The roasting production cycle is long (22-30 days for the first roasting and 5-20 days for the second roasting depending on the furnace type), and the energy consumption is high. The quality of the green body roasting has a certain impact on the quality of the finished product and the production cost; ② The coal tar pitch in the green body is coked during the roasting process, and about 10% of the volatile matter is discharged, and the volume shrinks by 2-3%, and the mass loss is 8-10%. The physical and chemical properties of the carbon blank also changed significantly. Due to the increase in porosity, the volume density dropped from 1.70g / cm3 to 1.60g / cm3, the resistivity dropped from about 10000μΩ.m to 40-50μΩ.m, and the mechanical strength of the baked blank was greatly improved. ③ Secondary baking is the process of baking the baked product again after impregnation to carbonize the asphalt impregnated in the pores of the baked product. Production of electric carbon bars with higher volume density requirements (all varieties except RP); ④ Main types of roasting furnaces: a continuous operation----ring furnace (with cover, without cover), tunnel kiln; b intermittent operation----downdraft kiln, car bottom roasting furnace, box roasting furnace; ⑤ roasting curve and maximum temperature: primary roasting----320, 360, 422, 480 hours, 1250℃; secondary roasting----125, 240, 280 hours, 700-800℃; ⑥ Inspection of roasted products: appearance knocking, resistivity, volume density, compressive strength, internal structure analysis.
[0066] Step S23: Preset carbon strip graphitization is completed by heating the carbon product to above 2300℃ in the protective medium in the high-temperature electric furnace, so that the amorphous chaotic layer structure carbon is converted into a three-dimensional ordered graphite crystalline structure. Planar hexagonal grid layered structure. The purpose and function of graphitization: ① Improve the electrical conductivity and thermal conductivity of carbon materials (resistivity is reduced by 4-5 times, and thermal conductivity is increased by about 10 times); ② Improve the thermal vibration resistance and chemical stability of carbon materials (linear expansion coefficient is reduced by 50-80%); ③ Make carbon materials have lubricity and wear resistance; ④ Expel impurities and improve the purity of carbon materials (the ash content of the product is reduced from 0.5-0.8% to about 0.3%). The graphitization of carbon materials is carried out at a high temperature of 2300-3000℃, so it can only be achieved in industry by electric heating, that is, the current directly passes through the heated roasted product. At this time, the roasted product loaded into the furnace is both a conductor that generates high temperature through the current and an object that is heated to high temperature. The furnace types widely used at present are Acheson graphitization furnace and internal heat series connection (LWG) furnace. The former has large output, large temperature difference and high power consumption, while the latter has short heating time, low power consumption, uniform resistivity but difficult to install joints. The control of the graphitization process is to determine the electric power curve corresponding to the temperature rise by temperature measurement. The power-on time is 50-80 hours for Acheson furnace and 9-15 hours for LWG furnace. Inspection of graphitized products: appearance knocking, resistivity test.
[0067] The specific detailed steps of step S3 are as follows:
[0068] Step S31: The purpose of mechanical processing of carbon bar material is to achieve the required size, shape, precision, etc. through cutting processing to make carbon bar that meets the use requirements. The body processing includes cutting and rough flat end surface, turning the outer bow shape and fine flat end surface.
[0069] Step S32: Cut a 1 mm thick and 100 mm wide pure titanium strip, place it in the carbon strip model, and put it into the carbon strip hoop edge.
[0070] Hereinafter, the method for manufacturing the pantograph slide plate of the present invention will be described in detail with reference to specific examples.
[0071] Example 1
[0072] The composition (wt%) of the high-purity carbon material used is as follows: C: 96.79; SiO2: 0.15; total iron (TFe): 0.20; ash: 0.2; volatile matter 0.8, particle size 150-200mu;
[0073] The asphalt components (wt%) used were as follows: C: 46.81, ash: 0.2, volatile matter 53.27;
[0074] The copper powder composition (wt%) used is as follows: Cu: 99.6, particle size 150-200mu;
[0075] The doped titanium carbide composition (wt%) used is as follows: Ti: 81.5, free C≤1, and particle size 150-200mu.
[0076] The mixing ratio is 81% high-purity carbon material, 16% asphalt, 1.5% copper powder and 1.2% titanium carbide, dry mixing for 25min to 35min, and drying for 20min after mixing evenly;
[0077] Then put the block mold into the vertical hydraulic press, match the pressure head with the mold, lift the baffle of the press, and feed the material in 2-3 times. The first press is carried out at 4-10MPa, the pressure is 20-25MPa, the time is 3-5min, and the second press is compacted. At the same time, vacuum is drawn. The pre-set carbon strip green body is protected by the filler and loaded into the lower loading electromagnetic induction graphitization sintering furnace for high-temperature graphitization roasting heat treatment to carbonize the coal tar in the green body. Graphitization sintering is carried out at 1250℃~2300℃, and the time is controlled. 23 days, after taking out of the furnace, the electrical properties and appearance are tested, the carbon bar density is ≤4.0g / cm3, the carbon bar flexural strength is ≥50MPa, the carbon bar compressive strength is ≥100MPa, the carbon bar impact toughness is ≥0.1J / cm2, the electrical characteristics are not less than 20℃ resistance is ≤12μΩ·m, the carbon bar is processed into suitable shape, cut and rough flat end surface treatment, turned outer bow processing and fine flat end surface treatment, cut 1mm thick and 100mm wide pure titanium strip, put it into the carbon bar model, and put in the carbon bar hoop edge.
[0078] Example 2
[0079] The composition (wt%) of the high-purity carbon material used is as follows: C: 96.79; SiO2: 0.15;
[0080] Total iron (TFe): 0.20; ash: 0.2; volatile matter 0.8, particle size 150-200mu;
[0081] The asphalt components (wt%) used were as follows: C: 46.81, ash: 0.2, volatile matter 53.27;
[0082] The copper powder composition (wt%) used is as follows: Cu: 99.6, particle size 150-200mu;
[0083] The doped titanium carbide composition (wt%) used is as follows: Ti: 81.5, free C≤1, and particle size 150-200mu.
[0084] The mixing ratio is 82% high-purity carbon material, 17% asphalt, 1.8% copper powder and 1.4% titanium carbide.
[0085] Dry mix for 25min to 35min, dry for 20min after mixing evenly, then place the block mold in the vertical hydraulic press, match the pressure head with the mold, lift the baffle of the press, feed in 2-3 times, implement 1st press at 4-10MPa, pressure 20-25MPa, time 3-5min, 2nd press compaction, and vacuum at the same time, put the preset carbon bar green body under the protection of the filler into the lower loading electromagnetic induction graphitization sintering furnace for high-temperature graphitization roasting heat treatment, so that the coal tar in the green body is carbonized, and graphitization sintering is carried out at 1250℃ to 2300℃, and the time is controlled for 23 days. After coming out of the furnace, the electrical properties and appearance are tested, the carbon bar density is ≤4.0g / cm3, the carbon bar flexural strength is ≥50MPa, the carbon bar compressive strength is ≥100MPa, the carbon bar impact toughness is ≥0.1J / cm2, the electrical characteristics are not less than 20℃ resistance ≤12μΩ·m.
[0086] Example 3
[0087] The composition (wt%) of the high-purity carbon material used is as follows: C: 96.79; SiO2: 0.15; total iron (TFe): 0.20; ash: 0.2; volatile matter 0.8, particle size 150-200mu;
[0088] The asphalt components (wt%) used were as follows: C: 46.81, ash: 0.2, volatile matter 53.27;
[0089] The copper powder composition (wt%) used is as follows: Cu: 99.6, particle size 150-200mu;
[0090] The doped titanium carbide composition (wt%) used is as follows: Ti: 81.5, free C≤1, and particle size 150-200mu.
[0091] The mixing ratio is 80.5% high-purity carbon material, 15% asphalt, 1.6% copper powder and 1.3% titanium carbide, dry-mixed for 25min to 35min, mixed evenly and dried for 20min, then placed in a block mold in a vertical hydraulic press, the pressure head matches the mold, the press raises the baffle, and feeds in 2-3 times, 4-10MPa for 1st press, 20-25MPa for 3-5min, 2nd press compaction, and vacuum at the same time, and the preset carbon bar green body is placed in the filler The green billet is put into the bottom-loading electromagnetic induction graphitization sintering furnace for high-temperature graphitization roasting heat treatment to carbonize the coal tar in the green billet, and graphitized at 1250℃~2300℃ for 23 days. The electrical properties and appearance are tested after it comes out of the furnace. The density of the carbon bar is ≤4.0g / cm3, the flexural strength of the carbon bar is ≥50MPa, the compressive strength of the carbon bar is ≥100MPa, the impact toughness of the carbon bar is ≥0.1J / cm2, and the electrical characteristics are not less than 20℃ resistance ≤12μΩ·m.
[0092] In summary, the method of the present invention can efficiently utilize the graphitization sintering and densification characteristics of high-purity carbon materials, asphalt, titanium carbide and copper powder, and has the advantages of stable conductive performance, good operation effect, long service life, low power consumption and low production cost.
[0093] In the description of the present application and its embodiments, it should be understood that the orientation or positional relationship indicated by the terms "top", "bottom", "height", etc. is based on the orientation or positional relationship shown in the accompanying drawings, and is only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.
[0094] In the present application and its embodiments, unless otherwise clearly specified and limited, the terms "set", "install", "connect", "connect", "fix" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection, an electrical connection, or a communication; it can be a direct connection, or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present application can be understood according to the specific circumstances.
[0095] In the present application and its embodiments, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may include the first and second features being in direct contact, or may include the first and second features not being in direct contact but being in contact through another feature between them. Moreover, a first feature being "above", "above" and "above" a second feature includes the first feature being directly above and obliquely above the second feature, or simply indicates that the first feature is higher in level than the second feature. A first feature being "below", "below" and "below" a second feature includes the first feature being directly above and obliquely above the second feature, or simply indicates that the first feature is lower in level than the second feature.
[0096] The disclosure above provides many different embodiments or examples to realize the different structures of the present application. In order to simplify the disclosure of the present application, the parts and settings of specific examples are described above. Of course, they are only examples, and the purpose is not to limit the present application. In addition, the present application can repeat reference numbers and / or reference letters in different examples, and this repetition is for the purpose of simplification and clarity, which itself does not indicate the relationship between the various embodiments and / or settings discussed. In addition, the various specific processes and material examples provided by the present application, but those of ordinary skill in the art can be aware of the application of other processes and / or the use of other materials.
[0097] Although the preferred embodiments of the present application have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications falling within the scope of the present application.
[0098] Obviously, those skilled in the art can make various changes and modifications to the present application without departing from the spirit and scope of the present application. Thus, if these modifications and variations of the present application fall within the scope of the claims of the present application and their equivalents, the present application is also intended to include these modifications and variations.
Claims
1. A method for manufacturing a pantograph slide plate, It is characterized in that The steps include: Step S1: mixing high-purity carbon material, asphalt, copper powder, and titanium carbide, and then adding a binder to form a five-component mixture; wherein titanium carbide is used as a dopant; Step S2: pressing and preforming the five-component mixture, and then pre-graphitizing and sintering it to obtain a pantograph carbon-based electrical contact material; Step S3: The surface of the pantograph carbon-based electrical contact material obtained by graphitization sintering is treated and conformed to form a carbon strip, and the carbon strip is embedded in the titanium pantograph mold to obtain a titanium lightweight high-speed rail pantograph slide plate.
2. The manufacturing method according to claim 1, It is characterized in that The carbon content of the high-purity carbon material is greater than or equal to 95.3% and less than 98.7% by weight; The carbon content of the asphalt is more than 45% by weight of fixed carbon; The content of copper element in the copper powder is not less than 99% by weight; The dopant is titanium carbide, the titanium content of the titanium carbide is greater than or equal to 83% by weight, and the free carbon is less than or equal to 1%; The binder is asphalt or polyvinyl alcohol.
3. The manufacturing method according to claim 2, It is characterized in that The proportion of the five-component mixture in the ingredients is as follows: The proportion of high-purity carbon materials is less than or equal to 58% and less than or equal to 70%; The proportion of asphalt is less than or equal to 13% and less than or equal to 17%; The proportion of copper powder is less than or equal to 2.5% and less than or equal to 4.5%; The proportion of titanium carbide is less than or equal to 2.5% and less than or equal to 4.5%; The proportion of adhesive is less than or equal to 12% and less than or equal to 16%.
4. The manufacturing method according to claim 2, It is characterized in that The proportion of the five-component mixture in the ingredients is as follows: The proportion of high-purity carbon materials is less than or equal to 62%; Asphalt accounts for less than or equal to 16%; The proportion of copper powder is less than or equal to 3.5%; The proportion of titanium carbide is less than or equal to 3.5%; The proportion of adhesive is less than or equal to 15%.
5. The manufacturing method according to claim 4, It is characterized in that In step S2, when the five-component mixture is pressed for pre-molding, the pressure is maintained at 400t; in step S2, a pre-graphitization sintering chamber is prefabricated, specifically, sintering at 1000°C for 6h in an electromagnetic induction sintering furnace, the heating curve is maintained at 200°C per hour, and the cooling curve is also maintained at 200°C per hour.
6. The manufacturing method according to claim 2, It is characterized in that In step S3, the pantograph carbon-based electrical contact material is embedded in the titanium pantograph mold, specifically: The pantograph carbon-based electrical contact material is embedded in the outer hoop edge metal frame, wherein the outer hoop edge metal frame is titanium metal with a purity greater than 99% and a thickness of 1.0 mm.
7. The manufacturing method according to claim 2, It is characterized in that In step S3, the surface of the pantograph carbon-based electrical contact material obtained by graphitization and sintering is processed and conformed, that is, turning and surface treatment are performed, and the processing amount does not exceed 10% of the total amount.
Citation Information
Patent Citations
Cathode carbon block for aluminum smelting purposes, and process for production thereof
CN102822392A
Carbon-metal composite material and its production
JP1994172029A
